2021
DOI: 10.1007/s00292-020-00899-1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Auswirkungen auf die Niere

Abstract: Bei einer schweren Coronavirus-Erkrankung-2019 (COVID-19) ist neben der Lungenerkrankung selbst das akute Nierenversagen (ANV) eine der häufigsten und schwerwiegendsten Komplikationen. Das SARS-CoV-2-Virus konnte hierbei auch in der Niere nachgewiesen werden. Patienten mit chronischen Nierenerkrankungen (CKD), dialysepflichtige sowie v. a. nierentransplantierte Patienten scheinen eine besonders vulnerable Population darzustellen. Die zunehmende Anzahl SARS-CoV-2-infizierter Patienten hat das Interesse an der g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition, in silico analysis performed on data sets of single-cell RNA sequencing revealed that RNA of genes that are considered to facilitate SARS-CoV-2 infection (i.e., RNA of ACE-2, transmembrane serine protease 2, and cathepsin L) are predominantly enriched in kidney cells. This enrichment suggested an increased susceptibility of renal cells to SARS-CoV-2 infection [ 234 , 235 ].…”
Section: Renal Implication In Covid-19 Diseasementioning
confidence: 99%
“…In addition, in silico analysis performed on data sets of single-cell RNA sequencing revealed that RNA of genes that are considered to facilitate SARS-CoV-2 infection (i.e., RNA of ACE-2, transmembrane serine protease 2, and cathepsin L) are predominantly enriched in kidney cells. This enrichment suggested an increased susceptibility of renal cells to SARS-CoV-2 infection [ 234 , 235 ].…”
Section: Renal Implication In Covid-19 Diseasementioning
confidence: 99%
“…A possible overinterpretation of postmortem clots as intravital thrombi has been discussed [38,45]. For organ-specific effects of SARS-CoV-2, the authors refer the reader to the relevant articles in this issue [2,3].…”
Section: Morphology Of Organ Damagementioning
confidence: 99%
“…A collection strategy should be developed and new specimens acquired in order to fill the gaps and to save material for future analysis. With regard to COVID 19, it became clear very rapidly that it was not just a lung disease but that other organs such as the heart [ 66 ] or kidney [ 67 ] are affected. With fast progress in medicine, reference material may be revisited some years later, as is also done currently with specimens from the collections.…”
Section: Discussionmentioning
confidence: 99%